The Role of Traditional Agroforest (Cinnamamon burmanii) to The Bird Conservation In Kerinci Seblat National Park. - Sartika, Dani; Subagyo, Agus; Sukmono, Tedjo (Universitas Jambi, 2009)
We undertook a research about the role of cinnamon agroforest in conserving bird inKerinci Seblat National Park. To observe the bird we used method of Indice Poctuale De'Abundance,whereas for the bird identification we employed some methods developed by Mckinnon ( 2001) andKing and Dickison (1993). As a control we also carried out the similar observation in the closed byprimary and secondary forest. The result shows that the bird diversity in cinnamon agroforest is notsignificant compare to that in primary and secondary forest (p>0.05). The index of bird diversity ( H') incinnamon agroforest and secondary forest is in medium class (3.3 and 3.49) while in the primary forestthe index is high (3.50).